2016
DOI: 10.1186/s12889-016-3774-6
|View full text |Cite
|
Sign up to set email alerts
|

The forgotten guidelines: cross-sectional analysis of participation in muscle strengthening and balance & co-ordination activities by adults and older adults in Scotland

Abstract: BackgroundIn 2011, the UK physical activity guidelines were updated to include recommendations for muscle strengthening and balance & coordination (at least two sessions of relevant activities per week). However, monitoring and policy efforts remain focussed on aerobic activity. This study aimed to assess differences by gender and age in the a) prevalence of muscle strengthening and balance & co-ordination guidelines, and b) participation in guideline-specific activities.MethodsThe sample for the muscle streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(137 citation statements)
references
References 36 publications
6
127
0
4
Order By: Relevance
“…A recent Australian national-representative sample study found only 5.5% of those aged 50 and over were meeting the recommended levels (Australian Government Department of Health, 2016) of muscle-strengthening activities per week (Bennie et al, 2016). Similar results have also been reported in Germany (Mayer et al, 2011), the United Kingdom (Strain, Fitzsimons, Kelly, & Mutrie, 2016) and…”
Section: Effectiveness Of Peers In Delivering Programs or Motivating supporting
confidence: 88%
“…A recent Australian national-representative sample study found only 5.5% of those aged 50 and over were meeting the recommended levels (Australian Government Department of Health, 2016) of muscle-strengthening activities per week (Bennie et al, 2016). Similar results have also been reported in Germany (Mayer et al, 2011), the United Kingdom (Strain, Fitzsimons, Kelly, & Mutrie, 2016) and…”
Section: Effectiveness Of Peers In Delivering Programs or Motivating supporting
confidence: 88%
“…However, compared to aerobic MVPA, as with other countries [23,24,33], the promotion of MSE has been of limited focus in previous Germany public health promotion [9]. Importantly, our study showed that compared to those reporting insufficient aerobic MVPA, greater proportions report insufficient MSE (70.6% vs. 54.7%).…”
Section: 0%) In Contrast Lower Mvpa-mse Guideline Adherence Estimentioning
confidence: 57%
“…Furthermore, the questionnaire items allow us to gain insight in the relative contribution of specific activities. To our knowledge, only few studies had this opportunity [25]. As far as we know, we are the first to combine yearly time points to assess long-term trends in adhering to a physical activity guideline and addressing activities that underlie changes over time.…”
Section: Adults and Oldermentioning
confidence: 99%